1992
DOI: 10.1021/ma00045a020
|View full text |Cite
|
Sign up to set email alerts
|

Atom-based modeling of amorphous 1,4-cis-polybutadiene

Abstract: The structure of amorphous 1,4-cis-polybutadiene is simulated with molecular mechanics and molecular dynamics subjected to periodic boundary conditions. All hydrogen atoms are explicitly taken into account. By means of the relaxation strategy which has been developed in this work, the low-energy states of relatively large systems can be reached within an acceptable computational time. With the five simulated structures, the distribution of bond angles, distribution of dihedral angles, and correlated distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
48
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 10 publications
8
48
0
Order By: Relevance
“…As far as the distributions of the torsion angles corresponding to dihedrals 1 and 2 are concerned, these were found to be in agreement with previous simulations studies such as those of Li and Mattice, 3 Smith and Paul, 9 and the recent EBMC simulation work of Gestoso et al 41 The distribution of dihedral φ 2 was seen to exhibit a maximum at around (118°and that of φ 1 at (180°and (60°( corresponding to the trans and gauche conformational states, respectively). It was further observed that as the temperature decreases (a) the height of the two torsionangle distributions at their peak increases (i.e., the relative population of states residing at the global minimum increases), (b) the population of the trans state (at (180°) in the distribution of the φ 1 dihedral increases accompanied by an increase in the population of the two gauche states, and (c) the trans population of φ 2 dihedral decreases.…”
Section: Resultssupporting
confidence: 91%
“…As far as the distributions of the torsion angles corresponding to dihedrals 1 and 2 are concerned, these were found to be in agreement with previous simulations studies such as those of Li and Mattice, 3 Smith and Paul, 9 and the recent EBMC simulation work of Gestoso et al 41 The distribution of dihedral φ 2 was seen to exhibit a maximum at around (118°and that of φ 1 at (180°and (60°( corresponding to the trans and gauche conformational states, respectively). It was further observed that as the temperature decreases (a) the height of the two torsionangle distributions at their peak increases (i.e., the relative population of states residing at the global minimum increases), (b) the population of the trans state (at (180°) in the distribution of the φ 1 dihedral increases accompanied by an increase in the population of the two gauche states, and (c) the trans population of φ 2 dihedral decreases.…”
Section: Resultssupporting
confidence: 91%
“…The edge length of the simulation cell was decided in the simulation depending upon the density and the total molecular weight of the three chains. This size of Downloaded by [Temple University Libraries] at 03:00 21 November 2014 the periodic box is greater than the sizes previously used in polybutadiene simulations [7][8][9] and satisfies the persistence length criterion [42] that the cell dimensions should be greater than twice the value of the persistence length of the polymer.…”
Section: Amorphous Cells For Glassy (300k) and Melt State (420 K)mentioning
confidence: 89%
“…The experimental value [44] of solubility parameter that is reported for polybutadiene (stereochemical composition not presented) is in the range 8.1-8.6 cal 1/2 /cm 3/2 . [41] The statistics on the individual values of the solubility parameter of the sample of structures here are acceptable on the basis of the standard deviation and by comparison with experimental data and with those available from earlier studies on such atomistic models [7,8,[21][22][23]28,42] for various polyolefins and slightly polar polymers.…”
Section: Atomistic Structure and Cohesive Energy Density Of 3d Bulkmentioning
confidence: 89%
See 2 more Smart Citations